G118(P) Living with chronic lung disease (cld); children and parents perspectives. (27th April 2015) - Bray, L; Shaw, NJ; Snodin, J
Abstract : Introduction: Caring for a premature baby who is oxygen dependant may result in short-term parental fatigue, anxiety, depression and restrictions to lifestyle, however long-term effects have not been reported. Aim: To investigate children and their parents' longer-term experiences of living with CLD. Methods: This was an exploratory qualitative study which collected interview data from children with CLD aged between 6 and 15 years of age (n = 10) and their parents (n = 12). Families were recruited from a children's hospital in the UK. Data were analysed inductively and thematically. Results: Children and their parents described that CLD was 'easier to live with as you get older'; this was in some cases due to symptoms becoming less severe but was also influenced by the strategies and expertise acquired in managing the condition. CLD was contextualised against other disabilities caused by prematurity and the uncertainty and fear which had overshadowed the first few years of the child's life. Parents had gained proficiency in accessing health services which demonstrated competency in dealing with CLD and bypassing those seen as less helpful. Parents felt anxious when they devolved responsibility for managing their child's condition to others, such as schools, and when they thought about their child's future. Children's concerns related to when CLD made them feel different to their friends by causing them to have to step-back, sit out and miss out on activities or when they were ostracised due to their short stature, respiratory symptoms or fatigue. Despite expertise in recognising and managing symptoms, children and their parents discussed a poor understanding of the nature of the condition and this influenced how they described CLD to friends, family, school and outside agencies. Many chose to call the condition asthma; the descriptor of CLD was seen as unhelpful and implied a contagious condition. Conclusions: Children and parents' accounts were mainly positive with CLD becoming easier to live with and manage over time. Ongoing concerns related to managing CLD outside the family, situations causing children to feel different and a poor understanding of the nature of CLD.